Ethical challenges experienced by public health nurses related to adolescents' use of visual technologies. (September 2019) - Laholt, Hilde; McLeod, Kim; Guillemin, Marilys; Beddari, Ellinor; Lorem, Geir
Background: Visual technologies are central to youth culture and are often the preferred communication means of adolescents. Although these tools can be beneficial in fostering relations, adolescents' use of visual technologies and social media also raises ethical concerns. Aims: We explored how school public health nurses identify and resolve the ethical challenges involved in the use of visual technologies in health dialogues with adolescents. Research design: This is a qualitative study utilizing data from focus group discussions. Participants and research context: We conducted focus group discussions using two semi-structured discussion guides with seven groups of public health nurses (n = 40) working in Norwegian school health services. The data were collected during January and October 2016. Discussions were audio recorded, transcribed, and coded into themes and subthemes using systematic text condensation. Ethical considerations: The leader of the public health nursing service who agreed to provide access for the study and the Norwegian Center for Research Data that reviewed and approved the study. All participants gave informed consent. Findings: In adolescents' use of visual materials with public health nurses, ethical concerns were raised regarding suicide ideations, socially unacceptable content, violation of privacy, and presentations of possible child neglect. The nurses utilized their professional knowledge and experience when identifying and navigating these ethical dilemmas; they resolved ethical uncertainties through peer discussion and collaboration with fellow nurses and other professionals. Discussion: We discussed the findings in light of Annemarie Mol's interpretation of the ethics of care. Mol expands the notion of ethical care to include the action of technologies. Conclusion: Although the increasing use of visual technologies offered benefits, school nurses faced ethical challenges in health dialogues with adolescents. To address and navigate these ethical issues, they relied on their experience and caring practices based on their professional ethics. Uncertainties were resolved through peer dialogue and guidance.